KEANEKARAGAMAN ARTHROPODA PERMUKAAN TANAH DI HUTAN LINDUNG DAN TAMAN WISATA ALAM KERANDANGAN LOMBOK BARAT - Immy Suci Rohyani dan B. Farista (Universitas Mataram, 2013)
AbstractThe aim of this research were to study the diversity of soil Arthropods in KerandanganProtected Forest and Natural Park; and to know the influence of environmental factors(physical and soil chemistry) on the abudance of soil Arthropods. This research wasconducted in Kerandangan Protected Forest and Natural Park. Soil arthropods were gatheredby PSM (metode perangkap sumuran/pitting trap method) and PCT (metode pencuplikantanah/soil sampling method).Identification to the artrophods captured by these methods wasdetermined until ordo level of classification, while data analysis was done by the use of HillBiodiversity Index. Soil Arthropods class that obtained by using PSM method are 5 classesand by PCT method are 6 classes. The total taxa of soil arthropods that obtained by usingPSM method was 25 taxa and by PCT method was 29 taxa. Formicidae, Hymenoptera other,Colembolla, Orthtoptera, Dermaptera weresoil Arthropod groups which are the most abundantand found in almost every location with PSM method. The Taxa obtained by PCT methodwere Acari, Hexapoda larva and Coleoptera.